2006
DOI: 10.3168/jds.s0022-0302(06)72123-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Experimental Mastitis Is Not Causal Toward the Development of Energy-Related Metabolic Disorders in Early Postpartum Dairy Cows

Abstract: Twenty Holstein cows in early lactation (7 d in milk) were administered 100 microg of Escherichia coli lipopolysaccharide (LPS) dissolved in 10 mL of sterile 0.9% NaCl saline (treatment; TRT) or 10 mL of sterile saline (control) into both right mammary quarters to test the hypothesis that acute experimental mastitis would have negative impacts on aspects of energy metabolism that might lead to the development of metabolic disorders. A primed continuous intravenous infusion (14-micromol/kg of BW priming dose; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
66
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 46 publications
(66 reference statements)
25
66
2
Order By: Relevance
“…An increased plasma insulin concentration in response to the LPS challenge in the present study is in agreement with previous studies (Waldron et al, 2003(Waldron et al, , 2006Vernay et al, 2012). Despite the inhibitory effect of insulin on glucagon secretion (Weir et al, 1976), plasma glucagon concentration increased after LPS challenge.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…An increased plasma insulin concentration in response to the LPS challenge in the present study is in agreement with previous studies (Waldron et al, 2003(Waldron et al, , 2006Vernay et al, 2012). Despite the inhibitory effect of insulin on glucagon secretion (Weir et al, 1976), plasma glucagon concentration increased after LPS challenge.…”
supporting
confidence: 93%
“…Intramammary LPS challenge did not affect plasma NEFA concentration in the present study. This finding is in agreement with a previous study that showed that intramammary LPS challenge did not affect plasma NEFA concentration, whereas plasma NEFA concentration increased in control cows that received NaCl (Waldron et al, 2006). The results of the present study are in contrast with a previous study where different doses of LPS were administrated intravenously for 100 min in mid-lactation dairy cows and plasma NEFA tended to increase after LPS challenge (Waldron et al, 2003).…”
supporting
confidence: 92%
See 3 more Smart Citations